PENGARUH TEKNIK ROLE PLAYING (BERMAIN PERAN) TERHADAP PENINGKATAN KEPERCAYAAN DIRI SISWA - Gutji, Nelyahardi; Yaksa, Rully Andi; Gultom, Tielsa (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
This study aims to determine how the influence caused by the role playing technique provided by the teacher on increasing student confidence. In this study using experimenta research with a quantitative approach. The sample amounted to 16 students for the experimental class and 16 students for the control class and if added up to32students. The analysis used used simple regression analysis and t-test. The results of this study obtained a significance value in the experimental class of 0.012 ≤0.05 through this value it can be concluded that there is an effect of role playing on increasing student confidence at SMP N 8 Jambi City. The calculated t value is 2.886≥t_table = 2.145, which means that there is an effect of role playing on increasing student confidence at SMP N 8 Jambi City.